QTL Mapping of Adult Plant Resistance to Stripe Rust in a Doubled Haploid Wheat Population - Tehseen, Muhammad Massub; Tonk, Fatma Aykut; Tosun, Muzaffer; Randhawa, Harpinder Singh; Kurtulus, Ezgi; Ozseven, Izzet; Akin, Behyan; Nur Zulfuagaoglu, Ozge; Nazari, Kumarse (Frontiers in Genetics, 2022)
Stripe rust caused by Puccinia striiformis Westend. f. sp. tritici. is a major bread wheat disease worldwide with yield losses of up to 100% under severe disease pressure. The deployment of resistant cultivars with adult plant resistance to the disease provides a long-term solution to stripe rust of wheat. An advanced line from International Winter Wheat Program (IWWIP) 130675 (Avd/Vee#1//1-27-6275/Cf 1770/3/MV171-C-17466) showed a high level of adult plant resistance to stripe rust in the field. To identify the adult plant resistance genes in this elite line, a mapping population of 190 doubled haploid (DH) lines was developed from a cross between Line 130675 and the universal stripe rust susceptible variety Avocet “S”. The DH population was evaluated at precision wheat stripe rust phenotyping platform, in Izmir during 2019, 2020 and 2021 cropping seasons under artificial inoculations. Composite interval mapping (CIM) identified two stable QTLs, QYr.rcrrc-3B.1 and QYr.rcrrc-3B.2, which were detected in multiple years. In addition to these two QTLs, five more QTLs, QYr.rcrrc-1B, QYr.rcrrc-2A, QYr.rcrrc-3A, QYr.rcrrc-5A and QYr.rcrrc-7D were identified which were specific to the cropping year (environment). All QTLs were derived from the resistant parent except QYr.rcrrc-3A. The significant QTLs explained 3.4% to 20.6% of the phenotypic variance. SNP markers flanking the QTL regions can be amenable to marker-assisted selection. The best DH lines with high yield, end-use quality and stripe rust resistance can be used for further selection for improved germplasm. SNP markers flanking the QTL regions can aid in identifying such lines.